PERTANGGUNGJAWABAN KORPORASI SEBAGAI PELAKU TINDAK PIDANA - Anjari, Warih (E-Journal Widya Yustisia, 2018)
The corporation is the subject of a criminal act. As the subject of criminal law corporation does not have an inner attitude. As for the criminal charges can accountability their required mens rea / Schuld. Crimes committed so damaging to the corporation and the state. While conventional accountability system that is individualized, direct and based on Schuld, difficult to apply to the corporation. The purpose of writing is to analyze the system of corporate accountability in order to convict the corporation, and constraints convict against the corporation. The method used is the statute approach (approach legislation) and case approach (case approach), methods of analysis using qualitative analysis to interpretation, and the data collection method using a literature study (library research). It can be concluded that the corporation can be justified by using a system of absolute liability and replacement; and the problem is the application of conventional criminal liability system and the difficulty of proving fault corporation. It is suggested that there is a shared understanding among law enforcement about corporations can be punished.